Comparative morphological and anatomical features of Haloxylon aphyllum and Haloxylon persicum of Ile-Balkhash region (Experimental biology, 2015)
The article describes the anatomical and morphological characteristics of representatives of the family Chenopodiaceae: Haloxylon aphyllum Minkw., Haloxylon persicum Bng. Identified similarities and differences in the anatomy of the stem of both species. The main difference is the number of layers of the epidermis: Haloxylon aphyllum – 1 layer, H. persicum – 3 layers. Due to changes in the epidermis of H. persicum increases the thickness of the epidermal layer. Haloxylon persicum has a thickness of the epidermis – 12,79-13,62 microns, while H. aphyllum – 7,67-10,53 mm. Comparative characteristics of the two species of Haloxylon shows some features of adaptation of psammophytes and halophytes. Features of the anatomical structure of the vegetative organs of plants, adequately reflect their adaptation to growing conditions. Studied species are plants-С4, by type of fixation О2, as a mechanism of adaptation to hot and dry climate. Haloxylon persicum regarded as a genetic derivative H. aphyllum.
Keywords: Haloxylon aphyllum Minkw.; Haloxylon persicum Bng.; anatomical structure; С4-plants; ecological adaptation